Analysis of China’s English Curriculum Standards for Compulsory Education from the Perspectives of Self-regulated Learning - Zou, Fengmei; Zhiyu, Cui; Qiucheng, Lin; Rou, Li; Sitong, Sun; Jiaying, Zheng; Renli, Zheng; Siqiong, Zhong; Xiaohua, Zhu (Gipan, 2024)
This paper analyzes the English Curriculum Standards for Compulsory Education (2022 Edition) developed and implemented by the Ministry of Education in China. We used Self-regulated Learning as a perspective in analyzing the curriculum standard and identified several elements of Self-regulated Learning emphasized in the document. This paper further elaborates how an inclusion of self-regulation is aimed at enhancing the teaching and learning of English as a foreign language in China. It presents the stages and sub-processes of self-regulated learning, in analyzing the curriculum standard. In this qualitative text analysis, the findings have been reported on thematic basis using the self-regulated learning framework and the elements that facilitate self-regulation. The findings show that English education under the guidance of the Standards attaches high importance towards stimulating learners’ autonomy and cultivating their self-regulated learning ability. This finding has an important implication for the future teaching and learning of English as a foreign language in China as such a policy focus on the self regulation can lead towards an improved engagement of the English learners in schools.